2020
DOI: 10.1016/j.celrep.2020.107993
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 Regulates MYB to Increase γ-Globin in Response to Loss of β-Globin

Abstract: Highlights d Loss of b-globin leads to upregulation of g-globin via altered ATF4 signaling d Reduced ATF4 decreases the levels of MYB and BCL11A d ATF4 induces MYB through binding at the HBS1L-MYB intergenic enhancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…HUDEP2 cells are a commonly used tool for studying globin regulation [ 4 , 25 , 26 , 27 ]. We constructed a cellular model of HBB homozygous knockout in HUDEP2 cells, hereafter referred to as HBB-KO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HUDEP2 cells are a commonly used tool for studying globin regulation [ 4 , 25 , 26 , 27 ]. We constructed a cellular model of HBB homozygous knockout in HUDEP2 cells, hereafter referred to as HBB-KO.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal hemoglobin (HbF, α 2 γ 2 ) is comprised of two copies of γ-globin ( HBG1/2 ) and two copies of α-globin ( HBA ), while adult hemoglobin (HbA, α 2 β 2 ) is comprised of two copies of α-globin ( HBA ) and two copies of β-globin ( HBB ) [ 2 , 3 ]. The HBG1/2 gene is primarily expressed during development, but silenced soon after birth and replaced by HBB expression [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…3A). 56,57 Two previous studies revealed that ATF4 serves as an important regulator of globin expression. 56,57 Depletion of ATF4 or disruption of the ATF4-binding motif in the +55kb enhancer in CD34+ HSPCs silences BCL11A expression in the erythroid lineage, resulting in increased production of fetal γ-globin protein in differentiated red blood cells.…”
Section: Xnls Enaspcas12a Efficiently Edits Genetic Regulatory Elemen...mentioning
confidence: 99%
“…(chr11:5273147), by whole genome sequencing (WGS) analysis. [10][11][12] In addition, significantly changed mRNA levels of the four transcription factors for Hb F expression were identified in the patient compared to his sister, by RNA-sequencing, including increased expression levels of TAL1, ATF2, and ATF4, which act as positive regulators of Hb F levels, [13][14][15] and decreased LYAR, which is essential for silencing the γ-globin gene. 16 Likewise, qPCR assay further validated the altered expression of these four genes in the patient (Figure S1(C), methods in Appendix S1).…”
mentioning
confidence: 98%
“…2 Prominently, several single-nucleotide polymorphisms (SNPs) associated with high Hb F levels were identified in the index, including rs7719521 (chr5:151049404), rs4910742 (chr11:5306509), rs1391619 (chr11:5455929), rs2855123 (chr11:5277078), and rs2855126 (chr11:5273147), by whole genome sequencing (WGS) analysis. [10][11][12] In addition, significantly changed mRNA levels of the four transcription factors for Hb F expression were identified in the patient compared to his sister, by RNA-sequencing, including increased expression levels of TAL1, ATF2, and ATF4, which act as positive regulators of Hb F levels, [13][14][15] and decreased LYAR, which is essential for silencing…”
mentioning
confidence: 99%